COI gene‐based mitochondrial DNA variation of horseshoe crab (Tachypleus gigas) reveals high genetic variation and occurrence of distinct populations in the Bay of Bengal, India, and its comparison with other populations. (1st February 2022) - Tudu, Sanatan; Gupta, Sandeep Kumar; Dash, Bisnu Prasad
Abstract: Horseshoe crab ( Tachypleus gigas ) is an archaic group of marine species which plays a vital role in the saline ecosystem. We attempted to develop a baseline database about the ecology, phylogeography, and genetic variation among the horseshoe crab population from Odisha, India. We collected 152 samples of horseshoe crab from the coastal area of the Bay of Bengal. The generated cytochrome c oxidase subunit I gene ( COI ) sequences of T .  gigas were compared with the GenBank sequences of five populations from Bangladesh, Thailand, Singapore, South China, and Malaysia. A total of 33 unique haplotypes were observed in six populations of T .  gigas . Pairwise F ‐statistic distance ( F ST ) between South China‐India, Malaysia‐India, Singapore‐India, Thailand‐India, and Bangladesh‐India were 0.021, 0.020, 0.017, 0.015, and 0.008, respectively. It indicated that the Indian and Bangladesh populations were genetically close and distinct from the other four populations. Furthermore, the migrant per generation (Nm) was 0.16, which indicated a low gene flow among T .  gigas populations. The haplotype diversity ( H d) and nucleotide diversity ( π ) were 0.7482 and 0.00313, respectively. It signifies the ecological importance of the Indian population that would help in formulating the future strategy for the conservation of horseshoe crab.